G20 as an initiative in strengthening global economic connectivity, digital security, and digital entrepreneurship: The case of Indonesia’s presidency - Djuyandi, Yusa; Azmi, Mohammad Fazrulzaman; Sudirman, Arfin; Bhakti, Agus; Siddha, Arlan; Ridzuan, Abdul Rauf (Research Journal in Advanced Humanities, 2026)
Indonesia’s G20 Presidency took place during a critical period of global recovery following the COVID-19 pandemic, when digital transformation became central to economic resilience and sustainability. This study aims to examine how and why Indonesia’s political initiatives within the G20 contribute to strengthening global economic connectivity, digital security, and the development of digital entrepreneurship. Employing a qualitative research design, the study utilizes observation and document analysis of G20 policy documents, declarations, and related official records to examine the relationship between post-pandemic global challenges and Indonesia’s policy agenda. The findings indicate that Indonesia’s G20 Presidency promotes a more inclusive global economic discourse by emphasizing digital connectivity, secure digital ecosystems, and the empowerment of digital entrepreneurs, particularly in developing countries. These initiatives enhance the participation of developing economies in global markets, support MSME resilience, and reduce digital disparities through improved infrastructure, skills, and policy coordination. Overall, the study demonstrates that Indonesia’s political initiatives within the G20 play a significant role in advancing inclusive and sustainable global economic recovery through digital transformation.